Women in Supramolecular Chemistry Collectively Crafting the Rhythms of Our Work and Lives in STEM - Leigh, Jennifer (Policy Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Drawing on research carried out by the Women in Supramolecular Chemistry (WISC) network, this book sets out the extent to which women working in STEM face inequality and discrimination. The authors use approaches more commonly associated with social sciences, such as creative and reflective research methods, to shed light on the human experiences lying behind scientific research. They show how this approach helps make sense of difficult personal experiences and to create a culture of change